COVID-19 decontamination procedures for photographic equipment in a secondary care setting. (1st October 2020) - Zoltie, Timothy; Owen, Katie; Devigus, Alessandro; Kelly, Sharon
Abstract: This article provides an overview of how long COVID-19 (SARS-CoV-2) survives on the built environment, and reviews currently available resources to provide recommendations on effective decontamination of photographic equipment based within a secondary care setting.